PENERAPAN MODEL UTAUT DALAM SISTEM PEMBELAJARAN E-LEARNING - Erma Delima Sikumbang (Paradigma, 2014)
E-learning  is  one  of  the  technologies  used  for  online  learning  students.  With  the  e-learning process of students learning is no longer limited by space and time as it can be accessed anywhere and anytime quickly and easily. This study describes the results of research on the factors affecting the  e-learning  system  with  approaches  Unified  theory  of  acceptance  and  use  of  technology (UTAUT).  Variables  used  in  this  study  consists  of  exogenous  and  endogenous  variables. Exogenous  variables,  namely,  performance  expectancy,  effort  expectancy,  social  influence  and facilitating  conditions  and  behavioral  intentions  are  endogenous  variables  and  user  behavior. These  results  indicate  that  performance  expectancy  has  a  positive  and  significant  correlatio (p=0.570)  to behavioral  intention as well as  facilitating  condition has a positive and  significant correlation (p=0.612)  to use behavioral.